Children of 6 years in formal spaces of education, manifestations and cultural productions - Pereira, Meira Chaves [UNESP] (Univ Fed Sao Carlos, 2021)
This work aimed to analyze the manifestations and cultural productions of five and six-year-old children in formal spaces of education. To perform this research, we used as methodology the qualitative approach based on participant observation, interviews and informal conversations with the children in a 1st year elementary school class with 25 children aged between five and seven years. The researcher built a field diary that was an important instrument for records of discoveries and interactions. The times and spaces of children's practices with and without teacher mediation and the manifestations and cultural productions of children during the period in which they remained in the school institution were analyzed. It was concluded that the manifestations and cultural productions of children are improved in the relationship with each other and add meanings and values both for the relationships between play, toys and games, when for life in society.
Keywords: Children's culture; Children's practices; Childhood; Early childhood education